Optimized Polymer Electrolyte Membrane Fuel Cell Electrode Using TiO2 Nanotube Arrays with Well-Defined Spacing - Özkan, Selda; Valle, Francesco; Mazare, Anca Valentina; Hwang, Imgon; Taccardi, Nicola; Zazpe, Raul; Macak, Jan M.; Cerri, Isotta; Schmuki, Patrik (ACS Applied Nano Materials, 2020)
TiO2-based catalyst supports in polymer electrolyte membrane fuel cells (PEMFCs) are widely investigated and provide an alternative to corrosion-susceptible carbon-based catalyst supports. For PEMFCs, designing a catalyst support material with an optimal geometry is of high importance to provide high catalyst dispersion, long-term operation, and efficient fuel cell performance. In this work, we report on the use of spaced (SP) TiO2 nanotubes (NTs) as catalyst support for the cathode electrode of PEMFCs. We construct a vertically aligned Pt-TiO2 NT catalyst layer on the Nafion membrane by a threestep process: (i) growth of self-organized TiO2 nanotubes with defined intertube spacing and detachment from the Ti substrate, (ii) Pt catalyst decoration on tube walls by atomic layer deposition (ALD) or photodeposition (PD), and (iii) decal transfer of the Pt-TiO2 catalyst layer onto Nafion to fabricate a membraneelectrode assembly (MEA) by hot pressing. Such an MEA configuration based on vertically aligned high aspect ratio spaced TiO2 nanotubes with Pt catalyst decoration delivers a significantly higher fuel cell performance, compared with close-packed (CP) TiO2 nanotubes. The key for this excellent performance is that TiO2 NTs with a regular interspacing on the Nafion polymer membrane enable highly dispersed Pt catalyst decoration and provide strongly enhanced mass transport in the interspaces.
CRIS-Team WoS Importer:2020-06-19